On soft P_c-connected spaces - Hamko, Qumri H.; Ahmed, Nehmat K.; Khalaf, Alias B. (Iraqi Journal of Science, 2020)
In this paper, we define the concept of soft -connected sets and soft -connected spaces by using the notion of soft -open sets in soft topological spaces. Several properties of these concepts are investigated.